Transpersonal Leadership in Action : How to Lead Beyond the Ego. - Enright, Duncan; Knights, John; Grant, Danielle; Young, Greg. ([Place of publication not identified] : Routledge, 2022)
How can leaders promote diversity, equality and inclusion? What does it mean to let go of leadership? How do learning, feedback and coaching help us become better leaders? Following the success of Leading Beyond the Ego, this book shows how to apply Transpersonal Leadership - practiced leaders who are radical, ethical, authentic and act beyond their own interests to create high-performing organisations - in a wide range of contexts. It considers the attributes of transpersonal leaders and how they transform organisations by building strong, collaborative relationships and a caring, sustainable and performance enhancing environment. Shining a light on the way forward for senior leaders, HR and talent professionals, the book covers: Characteristics of transpersonal leaders such as purpose, ethics, and adult development Impact of transpersonal leaders on global organisations, during digital transformation and change and through crises Case studies of transpersonal leadership in different contexts including in India and East Asia, when leading remotely, in HR and in politics Transpersonal Leadership in Action is essential reading for senior leaders, HR professionals, and those responsible for leader and organisational development.
Introduction: "Transpersonal Leadership in Action"Duncan Enright 1. Understanding Transpersonal LeadershipGreg Young, John Knights Part 1. Becoming a Transpersonal LeaderDuncan Enright 2. Purpose and Transpersonal LeadershipDanielle Grant, John Knights 3. Ethical Leadership: How to develop ethical leadersJohn Knights 4. Adult Development: Its Role in the Leadership JourneyAlison Hill, Heather Katz 5. Sustainable Leadership: Rewire Your Brain for Sustainable SuccessSue Coyne 6. Use of Feedback and Coaching to Improve Leadership and Emotional IntelligenceDuncan Enright 7. Women, Naturally the Best Leaders for the 21st Century?Greg Young 8. Learning Principles for Transpersonal Leadership DevelopmentDanielle Grant Part 2. Impact of a Transpersonal LeaderDuncan Enright 9. Developing Leaders for Global OrganisationsJenny Plaister-Ten 10. Addressing Diversity, Equality and Inclusion through Transpersonal LeadershipDanielle Grant, Frederick Hölscher 11. Digital Transformation and Change through Transpersonal LeadershipDuncan Enright 12. Managing Stakeholders Ethically - and Beyond the EgoJohn Knights13. Leading Through and Beyond CrisesDuncan Enright and Danielle Grant Part 3. Transpersonal Leadership in ActionDuncan Enright 14. Politics Beyond the Ego: Ethical Political Leadership for the 21st CenturyDuncan Enright 15. Leadership in India: Keeping Pace with India's Growth Story?Pavan Bakshi 16. Leadership in East Asia: Confucianism and Economics are inseparableMaiqi Ma 17. Remote Leadership Beyond the EgoDuncan Enright, Greg Young 18. How to develop Transpersonal leadership and transform organisational culture: A guide for HR ProfessionalsRob Jarvis 19. Letting Go of Leadership: A Hopeful Utopia for Corporate RealistsOtti Vogt
Keywords: BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Human Resources & Personnel Management; EDUCATION / Leadership; Leadership; Executive coaching